Synergistic Effects of Integrated Proprioceptive-Yogic Training on Physical and Psychological Performance in Female Handball Players: A Randomized Controlled Trial - Bhavani, M.; Suganya, S. (Journal of Neonatal Surgery, 2025)
The present study investigates the isolated and combined effects of proprioceptive training and yogic practices on performance-related fitness variables and psychological characteristics of female handball players. Recognizing the growing importance of both physical and psychological conditioning in sports performance, this study aimed to evaluate how targeted interventions in proprioceptive stimulation and yoga-based mind-body techniques influence agility, explosive power, endurance, breath-holding time, and self-confidence among athletes. A total of 60 female handball players were randomly divided into four groups: Proprioceptive Training Group (PTG), Yogic Practices Group (YPG), Combined Training Group (CTG), and Control Group (CG). The training interventions were conducted over a period of 8 weeks. Pre- and post-test data were collected using standardized fitness assessments and validated psychological scales. The data were analysed using Analysis of Covariance (ANCOVA) followed by Scheffé’s post hoc test to determine significant differences between groups. The results revealed that both isolated and combined training interventions significantly improved the selected physical and psychological variables, with the combined group showing the most substantial enhancements. These findings support the incorporation of integrated training protocols in handball to holistically enhance athlete performance and psychological resilience.